Integration of Faith and Morals in Islamic Education Management: A Case Study at MTs Nurul Islam Clekatakan - Abd Aziz Rois; Sukarman; Toi Akbari; Fuad fahmiy (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2024)
Islamic education plays a crucial role in shaping students' character through the integration of faith and moral values. However, challenges remain in effectively implementing these values ​​in schools, particularly in the context of educational management in madrasas. This study aims to analyze how faith and moral values ​​are integrated into the curriculum, learning, and school culture at MTs Nurul Islam Clekatakan. The research used a qualitative approach with a single case study design, involving data collection techniques through participant observation, in-depth interviews, Focus Group Discussions (FGDs), and document studies. Data analysis employed the Miles & Huberman interactive analysis model. The results indicate that the integration of faith in education at MTs Nurul Islam Clekatakan has successfully shaped students' morality, as evidenced by the increase in honest and responsible behavior among students. Daily practices based on faith, such as the Dhuha prayer and the